Electrolyte-resistant composition and application
Through the combination of silicate and sodium polyacrylate grafted starch, the viscosity reduction problem of sodium polyacrylate grafted starch in the electrolyte environment is solved, the electrolyte resistance performance and skin feeling are improved, the synergistic thickening effect is achieved, and the Its application in cosmetics and medicines.
Patent Information
- Application Number
- CN202411302278.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-17
AI Technical Summary
When using electrolyte components of sodium polyacrylate grafted starch, the solution viscosity is easily reduced, resulting in unstability of the product and affecting the use feeling. Adding other polymer thickening agents to control viscosity will lead to poor skin feeling.
Combine the low concentration of silicate with sodium polyacrylate grafted starch to improve its electrolyte resistance, and optimize the silicate content (0.01-5%) and sodium polyacrylate grafted starch content (0.01-5%) To maintain a refreshing skin feeling.
It improves the electrolyte resistance of sodium polyacrylate grafted starch, reduces the adverse effects of electrolytes on solution stability, achieves a synergistic thickening effect and a refreshing good skin feeling, and broadens its application range in cosmetics and medicines.
Smart Images

Figure BDA0005047998440000051 
Figure BDA0005047998440000061 
Figure BDA0005047998440000071
Abstract
Description
Technical Field
[0001] The present application relates to an electrolyte-resistant composition, in particular to an electrolyte-resistant composition comprising silicate and sodium polyacrylate grafted starch and application of the silicate. Background Art
[0002] Thickeners are a type of water-soluble polymer material. After being dissolved in water, the viscosity of the solution increases with the concentration. Thickeners are an important ingredient in cosmetic formulas to increase the viscosity of the product and affect the stability of the product and the skin's experience when used.
[0003] Sodium polyacrylate grafted starch has a thickening effect, and its refreshing skin feel makes it preferred to be added to cosmetics as a thickener. However, when sodium polyacrylate grafted starch is used, the viscosity of the solution is easily affected by electrolyte components and decreases, resulting in instability problems and affecting the final use experience. In order to alleviate the adverse effects of the decrease in system viscosity, other polymer thickeners with a certain viscosity are usually added to reduce the decrease in system viscosity. However, even if such an operation can control the viscosity at a certain level, it will make the skin feel worse.
[0004] Therefore, how to improve the tolerance of products containing sodium polyacrylate grafted starch to electrolytes while ensuring a refreshing skin feel is a technical problem that the present invention aims to solve. Summary of the invention
[0005] In order to solve the above-mentioned problems found in the present invention, the inventors of the present application unexpectedly discovered that compounding silicates that do not produce perceptible viscosity at low concentrations with sodium polyacrylate grafted starch can improve the electrolyte resistance of sodium polyacrylate grafted starch and provide a refreshing and good skin feel, thereby completing the present invention.
[0006] The specific technical solutions of this application are as follows:
[0007] In one aspect, the present application provides an electrolyte-resistant composition comprising silicate and sodium polyacrylate grafted starch as a thickener.
[0008] In some embodiments, the weight percentage of the silicate relative to the total weight of the composition is 0.01-5%, preferably 0.05-2.5%. When the content is greater than 5%, more preferably greater than 2.5%, it is difficult to obtain a refreshing skin feel, and it will contribute to the unpleasant feeling of rubbing mud during use. When the content is less than 0.01%, it is difficult to improve the electrolyte resistance of the sodium polyacrylate grafted starch.
[0009] In some embodiments, the weight percentage of the silicate relative to the total weight of the composition can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4. .7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5% or any range therebetween.
[0010] In some embodiments, the content of the sodium polyacrylate grafted starch is not particularly limited. For example, based on the total weight of the composition, the weight percentage of the sodium polyacrylate grafted starch is 0.01-5%, preferably 0.1-3%.
[0011] In some embodiments, the weight percentage of the sodium polyacrylate grafted starch relative to the total mass of the composition is 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6% , 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5% or any range therebetween.
[0012] In some embodiments, the silicate includes one or more of magnesium silicate, calcium silicate, aluminum silicate, magnesium aluminum silicate, lithium magnesium silicate, and / or lithium sodium magnesium silicate.
[0013] Preferably, the silicate comprises one or both of magnesium aluminum silicate and sodium magnesium lithium silicate.
[0014] More preferably, the silicate comprises magnesium aluminum silicate.
[0015] In some embodiments, the composition further comprises other thickeners, electrolyte components, etc.
[0016] In some embodiments, the other thickeners include one or more of ammonium acrylamide dimethyl taurate / VP copolymer, hydroxyethyl acrylate / sodium acryloyl dimethyl taurate copolymer, xanthan gum, hydroxyethyl cellulose, sclerotium gum, cellulose gum, and carbomer.
[0017] Preferably, the other thickeners include one or two of ammonium acrylamide dimethyl taurate / VP copolymer and hydroxyethyl acrylate / sodium acryloyl dimethyl taurate copolymer.
[0018] More preferably, the other thickener comprises ammonium acrylamidodimethyltaurate / VP copolymer.
[0019] In some embodiments, the weight percentage of the other thickener is 0.0001-2% relative to the total weight of the composition.
[0020] For example, based on the total mass of the composition, the weight percentage of the other thickener can be 0.0001%, 0.001%, 0.01%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% or any range therebetween.
[0021] In some embodiments, the electrolyte component includes one or more of an acid, a base, and a salt.
[0022] In some embodiments, the acid includes one or more of hydrochloric acid, phosphoric acid, citric acid, salicylic acid, ascorbic acid, lactic acid, azelaic acid, or derivatives thereof.
[0023] In some embodiments, the base includes hydroxide, carbonate, bicarbonate, ceramide MEA, and the like.
[0024] In some embodiments, the salt includes an inorganic salt, an organic salt, such as sodium chloride, potassium chloride, magnesium chloride, sodium acetate, or a salt formed by the aforementioned acid or base in a formulation system.
[0025] It should be noted that the composition of the present application can be prepared by a general method, wherein one or more diluents or carriers can be added, for example, any feasible water that can be used in the cosmetic field, such as deionized water, distilled water, ion exchange water, double distilled water, high-purity water, purified water, etc.
[0026] Furthermore, the composition can be used as an external product, preferably as a cosmetic or a medicine.
[0027] When it is a cosmetic, it can be various types such as facial cleansing products, facial masks, lotions, essences, emulsions, creams, foundations, etc. When it is a medicine, it can be made into various feasible external dosage forms, such as creams, solutions, etc., according to the methods of the prior art.
[0028] On the other hand, the present application also provides the use of silicate in improving the electrolyte resistance of sodium polyacrylate grafted starch.
[0029] In yet another aspect, the present application also provides use of silicate in improving the stability of products containing sodium polyacrylate grafted starch.
[0030] The relevant usage amounts in this application are only examples of technical effects. In actual use, technicians in this field can make corresponding additions based on actual needs, and no specific restrictions are made here.
[0031] The beneficial effects of this application include but are not limited to:
[0032] The present application compounds silicate and sodium polyacrylate grafted starch to improve the electrolyte resistance of sodium polyacrylate grafted starch and reduce the adverse effects of electrolytes on the stability of the solution system;
[0033] Furthermore, the present application compounds silicate and sodium polyacrylate grafted starch to obtain a synergistic thickening effect;
[0034] Furthermore, the present application compounds silicate and sodium polyacrylate grafted starch to obtain a refreshing and good skin feel;
[0035] Furthermore, on the basis of the compounding of silicate and sodium polyacrylate grafted starch, other thickeners with a refreshing skin feel may also be added;
[0036] Furthermore, based on the discovery of the above characteristics, silicate and sodium polyacrylate grafted starch can be combined and applied to external products, such as cosmetics and medicines, to give the products a certain viscosity, thereby broadening the application range of silicate and sodium polyacrylate grafted starch. DETAILED DESCRIPTION
[0037] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0038] If no specific conditions are specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The raw materials or instruments used, if no manufacturer is specified, are all conventional products that can be purchased commercially.
[0039] Example 1 Testing the Thickening Effect of Thickener
[0040] 1. Materials and instruments
[0041] The present application provides a general and / or specific description of the materials and instruments used in the experiments, and their sources are shown in the following Table 1. In addition, in the following examples, unless otherwise specified, % means wt%, i.e., weight percentage.
[0042] Table 1
[0043] Materials and instruments Model / Batch No. factory Viscometer DV2TRVTJ0 AMETEK BROOKFIELD Magnesium aluminum silicate VEEGUM HS Vanderbilt Minerals, LLC Sodium Magnesium Lithium Silicate LAPONITE-XLG XR BYK-Chemie GmbH Sodium polyacrylate grafted starch MAKIMOUSSE 25 DAITO KASEI KOGYO CO.,LTD.
[0044] 2. Testing process
[0045] According to Table 2, aqueous solutions containing silicate and sodium polyacrylate grafted starch were prepared to obtain samples 1#-27#, and viscosity tests were performed on them. The results are shown in Table 2.
[0046] The sodium polyacrylate grafted starch in sample 8# in Table 2 was replaced by ammonium acrylamide dimethyl taurate / VP copolymer to obtain sample 28#; the sodium polyacrylate grafted starch in sample 23# in Table 2 was replaced by ammonium acrylamide dimethyl taurate / VP copolymer to obtain sample 29#.
[0047] The estimated viscosity is the combined (cumulative) viscosity of the ingredients in the combination, where the viscosity of each ingredient is measured separately and it is assumed that they act independently. The estimated viscosity of a combination can be calculated using the following equation: Estimated viscosity = measured viscosity 1 + measured viscosity 2 + ... measured viscosity n (n is the number of active ingredients). When the measured viscosity is greater than the estimated viscosity, it indicates that the combination of the two has achieved a synergistic thickening effect. The greater the degree to which the measured viscosity is greater than the estimated viscosity, the better the synergistic thickening effect achieved by the combination of the two.
[0048] Table 2
[0049]
[0050]
[0051] 3. Conclusion
[0052] As can be seen from Table 2, when only silicate substances are used, the measured viscosity of the solution is below 100 cp, and it has a water-like texture, and therefore has no perceptible viscosity.
[0053] From the measured viscosity, it can be seen that silicate can increase the viscosity of the solution containing sodium polyacrylate grafted starch.
[0054] From the measured viscosity and estimated viscosity, it can be seen that compared with samples using a single silicate and a single sodium polyacrylate grafted starch, the combination of silicate and sodium polyacrylate grafted starch produces a viscosity that is much greater than the simple sum of the two when used alone, producing a synergistic thickening effect.
[0055] However, silicate has no effect of increasing the viscosity of the solution containing ammonium acrylamide dimethyl taurate / VP copolymer.
[0056] Example 2 Testing the electrolyte resistance of thickener
[0057] 1. Materials and instruments
[0058] Same as Example 1.
[0059] 2. Testing process
[0060] 0.5% sodium chloride was added to samples 1#-29# in Table 2 respectively and mixed evenly to obtain samples 1-29; 0.5% acrylamide dimethyl taurate ammonium / VP copolymer was added to sample 13# in Table 2, and then 0.5% sodium chloride was added and mixed evenly to obtain sample 30.
[0061] 0.5% potassium chloride was added to samples 2#, 6#, 9#, 13#, and 27# in Table 2, respectively, and mixed evenly to obtain samples 31-35.
[0062] Then samples 1-35 were subjected to viscosity tests, and the results are shown in Table 3.
[0063] The estimated viscosity is the combined (cumulative) viscosity of the components in the combination, where the viscosity of each component is measured separately and it is assumed that they act independently. The estimated viscosity of a combination can be calculated using the following equation: estimated viscosity = measured viscosity 1 + measured viscosity 2 + ... measured viscosity n (n is the number of active substances). When the measured viscosity is greater than the estimated viscosity, it indicates that the combination of the two still has a synergistic thickening effect in the electrolyte system and has good electrolyte resistance.
[0064] Table 3
[0065]
[0066]
[0067] 3. Conclusion
[0068] Combining Table 2 and Table 3, it can be seen that the viscosity of silicate substances in solutions with or without electrolytes is less than 100 cp, and has no perceptible viscosity.
[0069] From the measured viscosity in Table 3, it can be seen that silicate can improve the effect of electrolyte on the viscosity of the solution of sodium polyacrylate grafted starch, so that the solution has a perceptible viscosity change.
[0070] From the measured viscosity and estimated viscosity in Table 3, it can be seen that the combination of silicate and sodium polyacrylate grafted starch also produces a synergistic thickening effect, thereby improving the electrolyte resistance of the thickened composition.
[0071] Silicates do not improve the effect of electrolytes on the viscosity of the solution containing ammonium acrylamide dimethyl taurate / VP copolymer, and the viscosity of the combination of the two is below 100 cp, which does not have a perceptible viscosity. However, the combination of silicates, sodium polyacrylate grafted starch and ammonium acrylamide dimethyl taurate / VP copolymer can increase the viscosity of the solution and improve the problem of thickeners being intolerant to electrolytes.
[0072] Example 3 Skin feel test
[0073] 1. Experimental methods
[0074] Thirty testers applied samples 13 and 19 respectively and rated them based on five dimensions: (1) stickiness upon application, (2) residual sensation, (3) freshness, (4) absorption speed, and (5) stickiness after 2 minutes, with a score of 1-10. The higher the score, the stronger the feeling of this indicator. The average score was calculated as the final score.
[0075] 2. Experimental results
[0076] Table 4
[0077]
[0078] The results show that the samples of this application achieve a refreshing usage experience.
[0079] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.
Claims
1. An electrolyte-resistant composition, characterized in that Contains sodium silicate and polyacrylate grafted starch.
2. The composition according to claim 1, characterized in that Calculated relative to the total weight of the composition, the weight percentage of the silicate is 0.01-5%, preferably 0.05-2.5%.
3. The composition according to claim 1, characterized in that Calculated relative to the total weight of the composition, the weight percentage of the sodium polyacrylate grafted starch is 0.01-5%, preferably 0.1-3%.
4. The composition according to claim 1, characterized in that The silicate includes one or more of magnesium silicate, calcium silicate, aluminum silicate, magnesium aluminum silicate, lithium magnesium silicate and / or lithium sodium magnesium silicate.
5. The composition according to claim 1, characterized in that It also includes other thickeners and electrolyte ingredients.
6. The composition according to claim 5, characterized in that The other thickeners include one or more of ammonium acrylamide dimethyl taurate / VP copolymer, hydroxyethyl acrylate / sodium acryloyl dimethyl taurate copolymer, xanthan gum, hydroxyethyl cellulose, sclerotium gum, cellulose gum, and carbomer. Preferably, the weight percentage of the other thickener is 0.0001-2% relative to the total weight of the composition.
7. The composition according to claim 1, which is optionally used as an external product, preferably as a cosmetic or a medicine.
8. Application of silicate in improving the electrolyte resistance of sodium polyacrylate grafted starch.
9. The application of silicate in improving the stability of products containing sodium polyacrylate grafted starch.
Citation Information
Patent Citations
Thickener combination and application thereof in cosmetics
CN105078786A
Thickener composition and application thereof
CN106806159A
Skin care compositions comprising a terpolymer, process for preparing the same and method of use thereof
CN110662525A
Ion-resistant thickening agent as well as preparation method and application thereof
CN114306133A
Superabsorbent polymers and sunscreen actives for use in skin care compositions
US20130243836A1
